2013
DOI: 10.1021/bi400289e
|View full text |Cite
|
Sign up to set email alerts
|

Facile Heme Vinyl Posttranslational Modification in a Hemoglobin

Abstract: Iron-protoporphyrin IX, or b heme, is utilized as such by a large number of proteins and enzymes. In some cases, notably the c-type cytochromes, this group undergoes a posttranslational covalent attachment to the polypeptide chain, which adjusts the physicochemical properties of the holoprotein. The hemoglobin from the cyanobacterium Synechocystis sp. PCC 6803 (GlbN), contrary to the archetypical hemoglobin, modifies its b heme covalently. The posttranslational modification links His117, a residue that does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Although only a single His-heme cross-link was discovered in above two cyanobacteria Hbs, Lecomte and co-workers [70] showed that a second one can be readily created in PCC 6803 by introduction of a histidine close to the heme 4-vinyl group (L79H mutation) (Fig. 6A), His79-N ε -4-vinyl-C α , where His79 has an orientation analogous to that of His117 with respect to the heme 2-vinyl group.…”
Section: C-n Bondmentioning
confidence: 99%
See 3 more Smart Citations
“…Although only a single His-heme cross-link was discovered in above two cyanobacteria Hbs, Lecomte and co-workers [70] showed that a second one can be readily created in PCC 6803 by introduction of a histidine close to the heme 4-vinyl group (L79H mutation) (Fig. 6A), His79-N ε -4-vinyl-C α , where His79 has an orientation analogous to that of His117 with respect to the heme 2-vinyl group.…”
Section: C-n Bondmentioning
confidence: 99%
“…Since the formation of a His-heme cross-link occurs spontaneously in vitro under reducing conditions [70], construction of a His-heme cross-link is a potential strategy for design of new proteins with a non-dissociable heme cofactor. Recently, Lecomte and co-workers [71] showed the application in a eukaryotic globin, Chlamydomonas eugametos LI637 (CtrHb), which has less than 50% sequence identity with the cyanobacteria Hbs.…”
Section: C-n Bondmentioning
confidence: 99%
See 2 more Smart Citations
“…Engineering the covalent linkage to heme in other globins might also allow a new strategy to enhance heme stability. Such engineering of a covalent linkage has been attempted before but only in SynHb without the third linkage (H117A) for a different purpose at a different location and not in the classical globins (29).…”
mentioning
confidence: 99%